Optimization of Ultrasonic-assisted Extraction Using Taguchi Design and In vivo Activities of Polysaccharides from Flos populi - Ying Zhang (Science Faculty of Chiang Mai University, 2019)
There is an increasing demand for developing simple and efficient extraction of active polysaccharides from herbs, and ultrasound-assisted extraction (UAE) has attracted considerable interest. In this study, UAE of polysaccharides from Flos populi (PFP) was optimized using Taguchi L27 orthogonal design. The statistical analysis showed that the most important factors contributing to the extraction yield of PFP were liquid to solid ratio, extraction temperature, ultrasonic power and time, respectively, and the optimum conditions were at 25 mL/g, 50 °C, 400 W and 30 min which result the maximum yield of PFP (59.8 mg/g). At the above conditions, the extraction yield of 61.9 ± 2.5 mg/g was close to the predicted value. Moreover, the effect of extraction cycle (1-5) on the PFP yield was tested, and extraction cycle of 2 was determined. The UAE and conventional solvent extraction methods (CSE) were compared for extracting PFP. The UAE technique was very efficient in the extraction of PFP compared with CSE, for the similar yield of PFP was obtained at 60 and 150 min, respectively. Additionally, the antioxidant activities of PFP were accessed in-vivo. The results revealed that PFP had markedly enhanced the levels of catalase(CAT), glutathione peroxidase (GSH-Px) and superoxide dismutase (SOD), while decreased the level of malonaldehyde (MDA) in serums and livers of mice compared to CCl4 treated group. The study revealed that PFP possess potent antioxidant activity and could be useful for the development of new antioxidant agents.